2019
DOI: 10.1111/jmcb.12624
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of State‐Mandated Financial Education on College Financing Behaviors

Abstract: Students entering college have limited financial experience while making complex borrowing decisions. This paper examines a policy lever that may improve these decisions: high school personal finance graduation requirements. We use a difference-in-difference strategy to determine their effects on financial aid decisions of incoming freshmen at 4-year institutions. Our results suggest financial education shifts students from high-cost to low-cost financing. The requirements increase aid applications and accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 23 publications
0
33
0
1
Order By: Relevance
“…This suggests that potentially popular policies can spread across school networks within a state. Recent research finds that required personal finance in high school can improve credit scores (Urban et al, 2020;Brown et al, 2016), reduce delinquency (Urban et al, 2020;Brown et al, 2016), shift postsecondary education financing from higher to lower cost methods (Stoddard and Urban, 2020a), improve student loan repayment for first generation and low-income students (Mangrum, 2019), reduce alternative financial services borrowing (Harvey, 2019). Thus, understanding how to expand these course requirements, particularly in states without personal finance course mandates, can be important for improving the financial capability of young adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that potentially popular policies can spread across school networks within a state. Recent research finds that required personal finance in high school can improve credit scores (Urban et al, 2020;Brown et al, 2016), reduce delinquency (Urban et al, 2020;Brown et al, 2016), shift postsecondary education financing from higher to lower cost methods (Stoddard and Urban, 2020a), improve student loan repayment for first generation and low-income students (Mangrum, 2019), reduce alternative financial services borrowing (Harvey, 2019). Thus, understanding how to expand these course requirements, particularly in states without personal finance course mandates, can be important for improving the financial capability of young adults.…”
Section: Discussionmentioning
confidence: 99%
“…An additional literature considers quasi-experimental variation in graduation requirements by state and year. This research finds overwhelmingly positive effects of financial education on financial behaviors, including credit scores, delinquencies, payday borrowing, methods of financing postsecondary education, and student loan repayment (Mangrum, 2019;Urban et al, 2020;Stoddard and Urban, 2020b;Brown et al, 2016;Harvey, 2019). Though some states require personal finance instruction in high school, schools in the US largely operate with local control.…”
Section: Introductionmentioning
confidence: 96%
“…While less than half of states have ultimately been successful, the interest comes from both political parties and is not limited to a specific set of states. Third, previous research has shown that there are no clear economic conditions correlated with the implementation of financial education graduation requirements (Stoddard and Urban 2020).…”
Section: Empirical Strategymentioning
confidence: 95%
“…We build upon prior work that estimates the effects of personal finance graduation requirements in high school on the credit, debt, and savings decisions of adults (Brown et al 2016;Harvey 2019;Stoddard and Urban 2020;Urban et al 2020;Harvey 2020;Mangrum 2021). While we use a strategy similar to Stoddard and Urban (2020), we rely upon updates to the state policy data from Burke et al (2020).…”
Section: State Personal Finance Graduation Requirementsmentioning
confidence: 99%
See 1 more Smart Citation